The Tragedy of Religious Freedom - Marc O. DeGirolami (Harvard University Press, 2013)
Scholars of the law confront a predicament. To theorize about the lawâ€”to organize oneâ€™s ideas into generalities that capture real legal phenomenaâ€”is the peak of scholarly achievement. And with good reason, for when legal theory explains the world of law without distortion or caricature, when it refl ects crisply the legal worldâ€™s infi nite variety in subtle and elegant abstraction, it offers incomparable illumination. At its best, legal theory is a wonder, a pathway to wisdom. The trouble is that legal theoryâ€™s ambition to evaluate and pass judgment can suffocate its capacity to explain and understand. At its worstâ€”when it is puffed up with prideâ€”legal theorizing tends toward legal dogmatizing. In few areas is this propensity more pronounced than in the legal theory of religious liberty. The reasons are many but may be distilled to a single, fundamental incongruity. Legal theory seeks to fi x crystalline conceptual categories, the better to praise or condemn the lawâ€™s coercive demands. Legal theory is embarrassed by incoherence. It desperately wants to sort out and weigh up. Its critical eye is perpetually trained not only on the rules imposed by the law, but also, and inevitably, on the social and cultural objects of those impositions. But the social practice of religious liberty is resistant to legal theoryâ€™s self-assured, single-minded drive to evaluate, justify, and adjudge.For some time, and increasingly in recent years, scholars of religious liberty have criticized both the direction and coherence of the law.1 It is no exaggeration to say that Employment Division v. Smith,2 the Supreme Courtâ€™s most important religious liberty decision of the last two decades, is commonly viewed by scholars as one of the great disasters of the law of church and state.3 The doctrine encrusting the constitutional proscription against government â€œestablishmentâ€ of religion fares little better by their lights.4 Disaffection for their own fi eld, one might say, is unique in uniting them.